EFFECTIVENESS OF ELECTRONIC GOVERNANCE IN CRISIS MANAGEMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The research focuses on the role of electronic governance (e-Governance) in crisis management, highlighting the COVID-19 pandemic. Through a literature review and case studies analysis from various countries, including data on Bulgaria, this article explores how technologies support effective crisis management and offers ways to optimize electronic solutions in future crisis management strategies. The research methods include a qualitative analysis of data from publicly available sources, government reports, academic articles, and statistical data to identify successful practices and challenges in implementing electronic governance across different sectors during crises. The results show that Bulgaria has made significant progress in adapting and adopting electronic governance in response to the pandemic, highlighting the importance of technology in maintaining administrative functionality during crisis periods. The specific example of Chile, along with the Bulgarian experience in managing the pandemic, demonstrates the potential of technological solutions. The conclusions emphasize the need for developing flexible, scalable, and secure technological solutions for electronic governance, focusing on improving digital skills and infrastructure. Electronic governance has been identified as a key tool for crisis management that should be integrated into strategic crisis management plans. Future efforts should be directed towards enhancing technological platforms and developing innovative solutions for the resilience and efficiency of societies in crisis conditions.